Efficient whole‐brain tract‐specific T1 mapping at 3T with slice‐shuffled inversion‐recovery diffusion‐weighted imaging - Leppert, Ilana R.; Andrews, Daniel A.; Campbell, Jennifer S. W.; Park, Daniel J.; Pike, G. Bruce; Polimeni, Jonathan R.; Tardif, Christine L. (Magnetic resonance in medicine, 2021)
Purpose Most voxels in white matter contain multiple fiber populations with different orientations and levels of myelination. Conventional T1 mapping measures 1 T1 value per voxel, representing a weighted average of the multiple tract T1 times. Inversion‐recovery diffusion‐weighted imaging (IR‐DWI) allows the T1 times of multiple tracts in a voxel to be disentangled, but the scan time is prohibitively long. Recently, slice‐shuffled IR‐DWI implementations have been proposed to significantly reduce scan time. In this work, we demonstrate that we can measure tract‐specific T1 values in the whole brain using simultaneous multi‐slice slice‐shuffled IR‐DWI at 3T. Methods We perform simulations to evaluate the accuracy and precision of our crossing fiber IR‐DWI signal model for various fiber parameters. The proposed sequence and signal model are tested in a phantom consisting of crossing asparagus pieces doped with gadolinium to vary T1, and in 2 human subjects. Results Our simulations show that tract‐specific T1 times can be estimated within 5% of the nominal fiber T1 values. Tract‐specific T1 values were resolved in subvoxel 2 fiber crossings in the asparagus phantom. Tract‐specific T1 times were resolved in 2 different tract crossings in the human brain where myelination differences have previously been reported; the crossing of the cingulum and genu of the corpus callosum and the crossing of the corticospinal tract and pontine fibers. Conclusion Whole‐brain tract‐specific T1 mapping is feasible using slice‐shuffled IR‐DWI at 3T. This technique has the potential to improve the microstructural characterization of specific tracts implicated in neurodevelopment, aging, and demyelinating disorders.